2014
DOI: 10.4028/www.scientific.net/amr.1079-1080.309
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Construction Waste Brick Powder’s Activity

Abstract: Nowadays construction waste piles. For this phenomenon , this paper studied the mortar activity under different dosage of construction waste brick powder . The results show that with the increase of construction waste material content of brick powder, the mortar strength plummet .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…They also determined that mortars containing 5 and 10% brick powder had higher flexural strength than reference mortars at 90-day flexural strengths. The linear decrease in the 28-day flexural strengths with the increase in the brick powder replacement rate was also seen in similar studies by Liu [38] and Xue et al [39].…”
Section: Flexural Strengths Resultssupporting
confidence: 83%
“…They also determined that mortars containing 5 and 10% brick powder had higher flexural strength than reference mortars at 90-day flexural strengths. The linear decrease in the 28-day flexural strengths with the increase in the brick powder replacement rate was also seen in similar studies by Liu [38] and Xue et al [39].…”
Section: Flexural Strengths Resultssupporting
confidence: 83%
“…Ge et al [39] studied the long-term performance of concrete, and the results showed that the long-term performance (400 days) of concrete mixed with 10% or 20%RBP as a substitute for clinker was better, even better than ordinary Portland cement without RBP. Schackow et al [40] found that compared with the control group, the 28-day and 90-day compressive strength of mortar with RBP of 40% increased by 130% and 82%, respectively, and the compressive strength was inversely proportional to the apparent porosity. This indicates that the pozzolanic reaction [41] and micro-aggregate filling effect of RBP promote the development of compressive strength of mixed mortar when the content of RBP is appropriate.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…A reduction in the particle size of RBP accelerated the early hydration reaction and also decreased the setting time [26,27]. Lin [28] and Xue [29] studied the strength properties of cement-based materials using RBP with different substitution rates. Utilizing RBP as a partial substitution for cement resulted in a reduction in compressive strength.…”
Section: Introductionmentioning
confidence: 99%